Scholastic visual sports encyclopedia (New York Scholastic Reference, 2003)
Text and drawings explain the equipment and rules for approximately one hundred sports, including track and field, ball sports, and motor sports
Hurg
5
Keywords: Sports -- Encyclopedias, Juvenile; Sports -- Pictorial works -- Juvenile literature